Faktor-Faktor yang Mempengaruhi Kualitas Reviu Laporan Keuangan Pemerintah Daerah yang Dimemoderasi oleh Asistensi Keuangan - Hasana, Nur Azlia; Mahdalena, Mahdalena; Ronald S. Badu (Al-Buhuts, 2024)
This study aims to determine the effect of reviewer competence and time pressure on the quality of LKPD reviews moderated by financial assistance at the Inspectorate of North Gorontalo Regency and BPKP Gorontalo Province. The sampling technique used non-probability sampling of 84 APIP and primary data obtained from distributing questionnaires. The data were analyzed using the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach using smart PLS 3.0 software. The results of this study indicate that reviewer competence has a positive and significant effect on the quality of LKPD reviews, time pressure has a negative and significant effect on the quality of LKPD reviews, financial assistance can moderate (strengthen) the effect of reviewer competence on the quality of LKPD reviews, and financial assistance can moderate (weaken) the effect of time pressure on the quality of reviews of LKPD North Gorontalo Regency.